Allograft inflammatory factor-1 supports macrophage survival and efferocytosis and limits necrosis in atherosclerotic plaques. (October 2019) - Egaña-Gorroño, Lander; Chinnasamy, Prameladevi; Casimiro, Isabel; Almonte, Vanessa M.; Parikh, Dippal; Oliveira-Paula, Gustavo H.; Jayakumar, Smitha; Law, Calvin; Riascos-Bernal, Dario F.; Sibinga, Nicholas E.S.
Abstract: Background and aims: Allograft inflammatory factor-1 (AIF1) has been characterized as a pro-inflammatory molecule expressed primarily in the monocyte/macrophage (MP) lineage and positively associated with various forms of vascular disease, including atherosclerosis. Studies of AIF1 in atherosclerosis have relied on mouse models in which AIF1 was overexpressed in either myeloid or smooth muscle cells, resulting in increased atherosclerotic plaque burden. How physiologic expression of AIF1 contributes to MP biology in atherogenesis is not known. Methods: Effects of global AIF1 deficiency on atherosclerosis were assessed by crossing Aif1 −/− and ApoE −/− mice, and provoking hyperlipidemia with high fat diet feeding. Atherosclerotic plaques were studied en face and in cross section. Bone marrow-derived MPs (BMDMs) were isolated from Aif1 −/− mice for study in culture. Results: Atherosclerotic plaques in Aif1 −/− ;ApoE −/− mice showed larger necrotic cores compared to those in ApoE −/− animals, without change in overall lesion burden. In vitro, lack of AIF1 reduced BMDM survival, phagocytosis, and efferocytosis. Mechanistically, AIF1 supported activation of the NF-κB pathway and expression of related target genes involved in stress response, inflammation, and apoptosis. Consistent with this in vitro BMDM phenotype, AIF1 deficiency reduced NF-κB pathway activity in vivo and increased apoptotic cell number in atherosclerotic lesions from Aif1 −/− ;ApoE −/− mice. Conclusions: These findings characterize AIF1 as a positive regulator of the NF-κB pathway that supports MP functions such as survival and efferocytosis. In inflammatory settings such as atherosclerosis, these AIF1-dependent activities serve to clear cellular and other debris and limit necrotic core expansion, and may oppose lesion destabilization. Graphical abstract: Image 1 Highlights: AIF1 limits necrotic core expansion in atherosclerotic lesions. AIF1 supports macrophage survival and efferocytotic activities. AIF1 promotes NF-κB pathway activity in macrophages. AIF1 induces NF-κB-dependent stress response, inflammatory, and anti-apoptotic gene expression in macrophages. AIF1 promotes NF-κB pathway and limits apoptosis in atherosclerotic lesions in vivo.